Mitochondrial DNA sequence data reveals association of haplogroup U with psychosis in bipolar disorder. (January 2017) - Frye, Mark A.; Ryu, Euijung; Nassan, Malik; Jenkins, Gregory D.; Andreazza, Ana C.; Evans, Jared M.; McElroy, Susan L.; Oglesbee, Devin; Highsmith, W. Edward; Biernacka, Joanna M.
Abstract: Converging genetic, postmortem gene-expression, cellular, and neuroimaging data implicate mitochondrial dysfunction in bipolar disorder. This study was conducted to investigate whether mitochondrial DNA (mtDNA) haplogroups and single nucleotide variants (SNVs) are associated with sub-phenotypes of bipolar disorder. MtDNA from 224 patients with Bipolar I disorder (BPI) was sequenced, and association of sequence variations with 3 sub-phenotypes (psychosis, rapid cycling, and adolescent illness onset) was evaluated. Gene-level tests were performed to evaluate overall burden of minor alleles for each phenotype. The haplogroup U was associated with a higher risk of psychosis. Secondary analyses of SNVs provided nominal evidence for association of psychosis with variants in the tRNA, ND4 and ND5 genes. The association of psychosis with ND4 (gene that encodes NADH dehydrogenase 4) was further supported by gene-level analysis. Preliminary analysis of mtDNA sequence data suggests a higher risk of psychosis with the U haplogroup and variation in the ND4 gene implicated in electron transport chain energy regulation. Further investigation of the functional consequences of this mtDNA variation is encouraged.